Painéis de partículas homogêneas fabricados com resíduos lignoceluósicos e resina alternativa para aplicação em pisos - Do Nascimento, Maria Fátima; Lahr, Francisco Antonio Rocco; Christoforo, André Luis [UNESP]; Da Silva Bertolini, Marília; Fiorelli, Juliano; Da Silva, Márcio Rogério (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
Particleboards consist of composite materials with a wide range of applications, among these, for floors, where abrasion is an important property. This research aimed to investigate, with the aid of the Brazilian standard ABNT (2008), abrasion resistance (surface wear) of particleboards manufactured with waste of Eucalyptus sp. wood for employment on indoor environments floors. The factors investigated in the manufacture of the panels were resin type (castor oil-based polyurethane resin, urea formaldehyde), the use or not of varnish coating based on polyester, and the number of cycles for the abrasion test (1000; 1300; 1600), leading to a full factorial design with 12 different treatments. The responses investigated were the wear mass loss, wear mass loss percentage, wear loss in thickness and wear loss percentage in thickness. The results showed higher number cycles values then AC2 and AC3 classes, reaching 2700 cycles according to the loss mass. In the statistical analysis, only the number of cycles factor was significant in the investigated properties, which implies equivalence results for the other factors and interactions evaluated.
Homogeneous particleboards manufactured with lignocellulosic waste and alternative resin for floor applications
Keywords: Abrasion resistance; Particleboards; Resins